2005
DOI: 10.1056/nejmoa050753
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib in Previously Treated Non–Small-Cell Lung Cancer

Abstract: Erlotinib can prolong survival in patients with non-small-cell lung cancer after first-line or second-line chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

120
3,330
21
106

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,993 publications
(3,577 citation statements)
references
References 31 publications
120
3,330
21
106
Order By: Relevance
“…28,39,41,241,242 There are two well-established mechanisms of acquired resistance: additional mutations in the EGFR gene, acquired during the course of treatment, which change the protein coding sequence; and amplification of other oncogene signaling pathways, such as those involving the RAS and MET oncogenes. 84,[221][222][223] Kobayashi et al 182 reported a gefitinib-resistant advanced adenocarcinoma patient who had a relapse after 2 years of complete remission with gefitinib.…”
Section: Acquired Resistance To Egfr Tkimentioning
confidence: 99%
“…28,39,41,241,242 There are two well-established mechanisms of acquired resistance: additional mutations in the EGFR gene, acquired during the course of treatment, which change the protein coding sequence; and amplification of other oncogene signaling pathways, such as those involving the RAS and MET oncogenes. 84,[221][222][223] Kobayashi et al 182 reported a gefitinib-resistant advanced adenocarcinoma patient who had a relapse after 2 years of complete remission with gefitinib.…”
Section: Acquired Resistance To Egfr Tkimentioning
confidence: 99%
“…For example, in Caucasian patients, whose overall response rate is 10%, it seems highly sensible to use mutational status as a marker to select the 10-20% of patients who are most likely to benefit from anti-EGFR therapy. Yet, many studies have consistently reported 10% response rates to gefitinib and erlotinib in patients with wild-type EGFR, and the HR of erlotinib to placebo is 0.74 (Zhu et al, 2008), which is comparable to the overall survival benefit of erlotinib in all BR.21 patients (Shepherd et al, 2005). Therefore, it may be that one unifying predictive model does not apply to all patients with NSCLC, and that it is more practical to define different models for patients of various ethnicities.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…In the BR.21 study, erlotinib led to a significantly better response rate, median PFS and OS than placebo in the entire previously treated, unselected NSCLC patient population [10]. In the SATURN study, erlotinib maintenance therapy for non-progressive disease after first-line platinum treatment resulted in significantly longer median PFS for the whole study population, and also for the EGFR mutant subgroup [20].…”
Section: Discussionmentioning
confidence: 99%
“…Erlotinib (OSI 744, Tarceva ® , Genentech (Roche), USA) is a potent, orally administered epidermal growth factor receptor tyrosine-kinase inhibitor (EGFR-TKI), which is well tolerated and has been proven to prolong survival, delay symptom progression and improve quality of life versus placebo in patients with previously treated, advanced NSCLC in a large phase III trial (BR.21) [10,11]. Moreover, erlotinib is more effective as a firstline treatment than standard chemotherapy in patients with exon 19 deletions or exon 21 (L858R) substitution mutations of EGFR [12,13].…”
Section: Introductionmentioning
confidence: 99%